The factors of external environmental impact on a construction project - Strok, O.; Emelianova, O.; Tytok, V. (Ways to Improve Construction Efficiency, 2023)
The article highlights the factors of environmental impact on a construction project. It is determined that the success of the development and implementation of a construction project largely depends on the external environment and the quality of work of the participants involved in the process of development and implementation of a construction project. It is determined that environmental factors are divided into microenvironmental factors (in which a construction project is directly developed and implemented) and macroenvironmental factors (which include the general economic environment of the State and the region in which the construction project will be implemented, current legislation, tax system, credit policy, financial market conditions and the construction services market). It is found that modern building design is considered as a relatively independent step in the process of creating new socio-technical systems and processes, a kind of chain between research and production. It was found that each construction project has a list of specific goals and constraints. It is established that the practical experience of developing and implementing a construction project shows that attempts to reduce the cost of a project usually lead only to additional costs, which in some cases requires redevelopment of the construction project. The key stages of development of design and estimate documentation for a construction project are highlighted. It is determined that the effectiveness of a construction project reflects whether the construction project meets the goals and interests of the participants. The author finds that development and implementation of construction projects requires cooperation with state and local authorities, and that an important prerequisite for successful implementation of construction projects is the ability of local authorities to effectively fulfill their powers to provide quality services to developers. It is established that before starting construction, it is important to comply with legal and regulatory requirements and take into account the significant potential risks of construction contracts.